2005
DOI: 10.1007/s00068-005-2027-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results after Lower-Leg Replantation

Abstract: European Journal of Trauma Ab stractBackground: Although subtotal and total lower-leg amputation have been sucessfully replanted in the past, nowadays there is a common opinion that "these replantations do not justify their efforts, and therefore the patients should undergo primary amputation". Patients and Methods: In order to clarify this hypothesis, a retrospective clinical study of own cases operated on between 1981 -1998 and an extensive literature research we carried out. The following criteria were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In contrast, in 2002, Battiston et al [5] reported a 100% success rate of lower extremity replantation in nine patients, of whom 78% achieved functional success (Chen grade I or II). In 2005, Hierner et al [6] reported a 62.5% success rate in 15 total and subtotal amputated replantations, of which 92.7% were classified as showing functional success (Chen grade I and II). In a 2009 study by Cavadas et al [1] in Spain, the survival rate was 100% in 12 patients with 13 lower leg amputations who underwent replantation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in 2002, Battiston et al [5] reported a 100% success rate of lower extremity replantation in nine patients, of whom 78% achieved functional success (Chen grade I or II). In 2005, Hierner et al [6] reported a 62.5% success rate in 15 total and subtotal amputated replantations, of which 92.7% were classified as showing functional success (Chen grade I and II). In a 2009 study by Cavadas et al [1] in Spain, the survival rate was 100% in 12 patients with 13 lower leg amputations who underwent replantation.…”
Section: Discussionmentioning
confidence: 99%
“…The option to reconstruct an un-salvageable lower limb injury with a VCA is appealing but has traditionally been met with resistance due concerns around poor functional recovery, high-risk surgery and burden of immunosuppression. The on going debate in the field of VCA surrounding the risk: benefit ratio of lower limb VCA originates from the relatively poor functional results historically reported following lower limb replants [53,54]. However, after reports of good functional outcomes of upper limb transplants worldwide, even those at a midhumeral level, the concept of lower limb replant and the possibility of VCA were revisited [18,31,32].…”
Section: Lower Limb Transplantsmentioning
confidence: 99%